Is the ‘Martyrdom’ of Human Bombers a ‘Sacrifice’? - Ugo Fabietti (Antropologia)
The paper explores the phenomenon of martyrdom in the context of human bombings, emphasizing the interplay between individual sacrifice and collective ideology. It highlights the symbolic and communicative dimensions of these acts, where martyrdom serves both a political and transcendent purpose. The study delves into historical and contemporary perspectives, comparing Christian and Muslim martyrdom, and analyzing the motivations and societal impacts of such sacrifices. Through the lens of media representation and ritual practices, the document examines how these acts are perceived and legitimized within their respective communities.